The Effect of Audit Quality, Audit Committee, and Financial Stability on Financial Statement Fraud in Consumer Non-Cyclicals Manufacturing Companies Listed on the IDX 2020-2024 - Cindy Noya; Herawansyah Herawansyah (The Es Accounting And Finance, 2026)
This study aims to analyze the effect of audit quality, audit committee, and financial stability on financial statement fraud in consumer non-cyclicals manufacturing companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The study uses a quantitative approach with binary logistic regression methods on 310 observations selected using purposive sampling. Financial statement fraud is proxied using the Beneish M-Score and classified into a dummy variable. Audit quality is measured using a dummy variable based on the size of the Public Accounting Firm, Big 4 and Non-Big 4, the audit committee is measured by the proportion of members with accounting or finance expertise, while financial stability is proxied using changes in total assets (ACHANGE). The results show that audit quality and the audit committee do not affect financial statement fraud. On the other hand, financial stability does have an impact on financial statement fraud. The study's findings suggest that the audit quality and the audit committee require more comprehensive measurements to accurately represent the effectiveness of oversight functions, while financial stability is a relevant factor in explaining the occurrence of financial statement fraud.